Influence of Chemical Composition and Chrome Plating Duration on Thickness and Hardness of the Surface Coating on the Brass Plate - Syafrul Hadi (Jurnal Teknik Mesin (JTM), 2016)
In the metalworking technology, the electroplating process is categorized as a process of late. Electroplating can be interpreted as a metal coating process by using an electric current, wherein the anode used is chromium, but it also is the chemical composition that is acidic chromium, sulfuric acid, sulfuric and hydrochloric acid, are used to move the particles of the metal coating to the material to be coated , The objective of the research is to see the influence of the chemical composition of the solution to the thickness and hardness of the coating, the effect of long time coating thickness and hardness of the surface coating on the brass plate. Benefits of the research carried out to improve the quality of products in terms of physical, increase corrosion resistance, and increase violence. In this study specimens used rectangular brass plate with a size of 60 mm x 40 mm x 1.5 mm. Chromium electroplating process using a solution by varying the chemical composition of the solution and long plating time 20 minutes, 25 minutes and 30 minutes. Thickness testing conducted by means of Optical Microscope microstructure whereas hardness testing conducted by Micro Hardness Tester with a load of 9807 N. The results of this study showed that the thickness of the layer of the highest at 30 minutes with the chemical composition of the acid solution of chromium (CrO3) 200 grams / liter, sour sulphate (H2SO4) 30 g / liter of 32.85 μm while the highest hardness layer at the time of 25 minutes with the chemical composition of the acid solution of chromium (CrO3) 200 grams / liter, sulfuric acid (H2SO4) 30 g / liter of 112.67 VHN.